Panna Addams: współczesna tożsamość „z pogranicza”. O postawie głównej bohaterki serialu Wednesday - Pilawska-Gronostaj , Roksana (Studia Edukacyjne, 2024)
The article is a part of qualitative interpretive research conducted as part of a doctoral thesis addressing the portrayal of femininity in contemporary selected film fairytales. The aim of the analysis was to present fairy tale heroines as an audiovisual representation of expectations, norms, and values stemming from gender and inscribed in the prevailing socio-cultural order. The qualitative interpretation of the active stance of the main character in the popular series Wednesday serves as an exe mplification of cultural contestation between the traditional understanding of femininity and its androgynous redefinition, not constrained by widely accepted social norms.